PEMBINAAN KULTUR SEKOLAH SEBAGAI WUJUD PEMBENTUKAN KARAKTER DI SMP NEGERI 1 KEDAWUNG - Ismi Islamiati (FKIP Unswagati, 2025)
This study aims to determine the development of school culture in SMP Negeri 1 Kedawung. Observation subjects were principals, teachers, students, and parents. Observations were made per subject to see the situation and conditions. Observational data were analyzed descriptively qualitatively. Observation results show that SMP Negeri 1 Kedawung has implemented school culture optimally with collaboration between principals, teachers, and students. The school culture developed and fostered by the school is the 5S culture morning absence, morning tadarus, morning prayer and prayer, multidirectional communication, and love of culture. Characters that are grown from fostering school culture, namely discipline, religious, social care, honesty, love of reading, tolerance, love for the homeland, mutual respect, friendship, responsibility, and care for the environment. These characters must always be fostered in a sustainable manner so that all school personnel have noble personalities.' Keywords: School Culture, Student Character, Junior High School